Techniques de traduction dans le recueil de nouvelles traduites par des étudiants de la pédagogie du français dans le lot 2016 - Fauzul Muna; Dies Oktavia Dwi Astuti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
This research aims to describe what translation techniques translators use in translating translated texts and to find out what translation techniques are most dominantly used. The data in this research are words, phrases, clauses, or sentences from the French short story text Le Loup Garou and Icare and their translations in an anthology of translated short stories entitled Negeri Tak Berbunga by French Language Education students at Uinversitas Negeri Semarang batch 2016. Data was collected using the listening method, which was then followed by the note-taking method. For data analysis, the researcher used the matching method or continued using the technique of selecting certain elements or Pilah UnsurTertentu (PUP). It means that the researcher used his abilities to analyze the data. From the 18 translation techniques revealed by Molina & Albir (2002: 498-512), translators used 15 of them in translating the texts of Le Loup Garou and Icare. The dominant translation used by translators is literal (66.83%). The 15 translation techniques used are adaptation, borrowing, calculation, compensation, discursive creation, generalization, linguistic amplification, linguistic compression, literal translation, modulation, particularization, reduction, substitution, transposition, and variation.